Agronomic comparison of anhydrous ammonia applied with a high speed-low draft opener and conventional knife injection in corn - Woli, Krishna P.; Fernández, Fabián G.; Sawyer, John E.; Stamper, Joshua D.; Mengel, David B.; Barker, Daniel W.; Hanna, Mark H. (My University, 2014)
Anhydrous ammonia (AA) is an important N fertilizer in the U.S., and with large farming operations rapid application is needed. This study evaluated the impact of AA application timing and N rates when applied with a high speed low draft (HSLD) or a conventional till knife (CTKI) on corn (Zea Mays L.) production in no-tillage fields. The study was conducted at sites located in Illinois, Iowa, and Kansas from 2007 to 2009. The experimental design was a split-plot factorial arrangement of application method, timing (fall; spring preplant, SP; and sidedress, SD), and five N rates. Fall AA application was least efficient (mean 55 kg N haˉ¹ higher optimum N and 2% lower grain yield, GY), with SP and SD equivalent. The HSLD was comparable to the CTKI with most applications, except when high N rates (180 and 225 kg N haˉ¹) were applied SP. For these treatments AA injury reduced plant population (PP), early season growth, canopy NDVI, and GY. Seedling injury did not occur with any N rate or timing with the CTKI. Shallow AA placement at high speed with the HSLD can provide a viable alternative to traditional deeper knife injection when conditions are suitable for AA application and positioning avoids corn seedling injury. Anhydrous ammonia application with the HSLD, however, should be avoided where high SP AA rates may be placed directly under future corn rows.
Citation: Woli, Krishna P., Fabián G. Fernández, John E. Sawyer, Joshua D. Stamper, David B. Mengel, Daniel W. Barker, and Mark H. Hanna. “Agronomic Comparison of Anhydrous Ammonia Applied with a High Speed-Low Draft Opener and Conventional Knife Injection in Corn.” Agronomy Journal 106, no. 3 (2014): 881–92. https://doi.org/10.2134/agronj13.0441.
Keywords: Anhydrous ammonia; Fertilizer; High speed low draft; Conventional till knife; Fertilizer application